ONE FINANCIAL REPORTING GLOBAL LANGUAGE: THE ULTIMATE GOAL? - Limijaya, Amelia (Jurnal Riset Akuntansi dan Keuangan, 2017)
This article aims to analyse the extent to which international accounting standards is applied and whether it is the ultimate goal. Up until the end of 2016, approximately there are 84% of the 149 jurisdictions analysed which require IFRS for all or most domestic publicly accountable entities. This may indicate that we are not that much further from having a single set of globally-accepted accounting standards. However, there is more to financial reporting than just accounting standards alone, such as the political aspect of accounting standard-setting, translation issues surrounding IFRS adoption, the US position and the complexity of financial reporting. Improving financial reporting quality needs more than just having global accounting standards, rather, it is also essential to consider the preparers’ incentives and other institutions surrounding the firm. Stakeholders need to broaden the perspective when viewing financial reporting, so that it will not be focused merely on accounting standards alone.